Mediterranean Diet (MedDiet) and Lifestyle Medicine (LM) for support and care of patients with type II diabetes in the COVID-19 era: a cross-observational study - Cangelosi, Giovanni; Grappasonni, Iolanda; Nguyen, Cuc Thi Thu; Acito, Mattia; Pantanetti, Paola; Benni, Andrea; Petrelli, Fabio (Acta Biomedica Atenei Parmensis, 2023)
Introduction: Diabetes affects 425 million people worldwide (range 20-79 years). Of these, between 87% and 91% are affected by type 2 diabetes mellitus (DM2), and 79% live in medium/low income countries. Objectives: the main objective of the study was to observe, through the administration of specific questionnaires, the relationship existing between metabolic clinical parameters, quality of life of patients with DM2 and adherence to the MedDiet at first access to Diabetes Center in the period after the COVID-19 pandemic. The secondary objective was to observe the results obtained both qualitatively and quantitatively. Materials and Methods: the study was a cross-sectional study. Two types of questionnaires were administered; the first (Medi-Lite) that expresses with specific score the level of “Mediterraneanness” diet while the second concerns the assessment of the SF-36 quality of life. Quantitative data such as biochemical and anthropometric parameters were collected and, through multiple regression, based on the method of least squares (OLS Model) and through the Gretl open source software were analyzed. Results: fifty-two of the 90 patients at first access to the recruiting center in the period considered, met the inclusion criteria and and written consent. None of the estimated coefficients was statistically significant except Diastolic Blood Pressure (DBP), with a p-value < 0.0466. With an improvement in the level of “Mediterraneanness” there is a favorable relationship regarding creatinine, High-Density Lipoprotein (HDL), DBP and glycemia. Conclusions: The necessary post-COVID-19 territorial management cannot fail to take into consideration this new method of care which puts the patient and the community to which they belong at the center of the complex process of assistance.